2013
DOI: 10.1002/mana.201100263
|View full text |Cite
|
Sign up to set email alerts
|

On the multiplicity of nodal solutions of a prescribed mean curvature problem

Abstract: We prove existence and multiplicity results for sign‐changing solutions of a prescribed mean curvature equation with Dirichlet boundary conditions. Our arguments involve a perturbation of the degenerate part \documentclass{article}\usepackage{amssymb}\begin{document}\pagestyle{empty}$1/\sqrt{1+s}$\end{document}, which allows us to use classical variational techniques and to localize small regular solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 27 publications
0
6
0
12
Order By: Relevance
“…The following lemma is a variant of the well-known Moser iterative scheme, see for instance [2,18]. Lemma 2.4.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…The following lemma is a variant of the well-known Moser iterative scheme, see for instance [2,18]. Lemma 2.4.…”
Section: Preliminariesmentioning
confidence: 99%
“…In this paper, we deal with the question of the existence of weak solutions of the problem −div(a(|∇u| 2 )∇u) = λf (x, u) in Ω, u = 0 on ∂Ω, (1.1) where Ω is a bounded domain of R N with smooth boundary ∂Ω, N > 2, a : R → [0, ∞) is a continuous function, λ is a positive parameter, and f : Ω × R → R is a Carathéodory function which grows as |u| p−2 u near zero for 2 < p < 2 * . Since quasilinear equations serve as model of a wide class of differential operators, there has been a considerable amount of works on this subject (see [2][3][4]16] and references therein). For our purpose we consider two principal operators: a(t) ≡ 1 which reduces (1.1) to the Laplacian case, that is the scalar equation −Δu = λf (x, u); and a(t) = (1 + t) −1/2 where we obtain the mean curvature operator.…”
Section: Introductionmentioning
confidence: 99%
“…This approach originated in a series of works on the Dirichlet problem for semilinear equations, a review of which can be found in [4]. It has also been used more recently in the context of a prescribed mean-curvature problem in Bonheure et al [6], from which some of our arguments are inspired. Note that the Nehari approach stronlgy relies on the monotonicity assumption (g3), which is not needed in [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the work [6], the authors studied a related subcritical problem in which they obtained positive solutions. In the recent work [3], Bonheure, Derlet and Valeriola have studied a purely subcritical version of (P λ ), where they proved the existence and multiplicity of nodal H 1 0 (Ω) solutions, to sufficiently large values of λ. They overcame the difficulty in working in the BV (Ω) space, which is the natural functional space to treat (P λ ), by doing a truncation in the degenerate part of the mean-curvature operator in order to make possible construct a variational framework in the Sobolev space H 1 0 (Ω).…”
Section: Introductionmentioning
confidence: 99%
“…where • is the Sobolev norm in H 1 0 (Ω). Our approach follows the main ideas of Bonheure et al in [3], in order to make possible consider a related modified problem in H 1 0 (Ω). Afterwards, to get solutions of the modified problem we apply Krasnoselskii genus theory in the same way that Azorero and Alonso in [1].…”
Section: Introductionmentioning
confidence: 99%